FACTORS INFLUENCING GEERT WILDERS CREATING FITNA (2008): A BEHAVIORIST APPROACH - SANTOSO, AGUS (2011)
This study is aimed to show what factors that influenced Geert Wilders creating Fitna film (2008) by using behaviorist approach. It is done by establishing two objectives: The first is to analyze the film based on its structural elements and the second is to analyze the factors of the film creator creating his film based on behaviorist a pproach. The type of this research is qualitative research. The type of the data of the study is a film including its creator such as text, voice, audio, video, and etc. The sources of the data are divided into two types: primary and secondary data. The primary data source is Geert Wilders to analyze his factors for creating Fitna film. The secondary data source is his film entitled Fitna to analyze its structural elements. The result of the research comes to the following conclusions. First, based on the structural analysis of the Fitna film, the film contains 11 elements: writer, director, genre, country, runtime, language, theme, style, color, aspect ratio, and fun stuff. Second, based on behavioral analysis, the factors of Wilders creating Fitna film are divided into two factors: one internal factor and several external factors. One internal factor is Wilders’ own job/ position as the leader for Freedom Party that contrasts to the Muslims’ ideology. Several external factors are Qur’an rules, Muslims’ ideology, the demonstration of the Muslims, and etc.